FROM O GUARANI TO A ÚLTIMA FLORESTA: INDIGENOUS REPRESENTATIONS IN CINEMATIC HISTORY (Revista Internacional de Folkcomunicação, 2025)
The Brazilian Indianist movement of the 19th century, led by authors like José de Alencar, propagated an idealized image of the romantic and easily assimilable "Indian." This analysis aims to understand indigenous representations in Brazilian cinema through the films O Guarani (1996), based on Alencar's work, and The Last Forest (2021), directed by Luiz Bolognesi. From a decolonial perspective, the study explores how cinema reflects and perpetuates colonial stereotypes or promotes narratives that value indigenous identity. The theoretical framework includes works by Hollanda (2020), Moreira (2010), Lima (2006), and Quijano (2005).